Migration, factor mobility and economic complexity in African countries - Solomon O. Okunade; Oyindamola O. Adeyemo; Oluwole J. Adeyemi; Evans Osabuohien (Scientific African, 2025)
The African region's ability to diversify and become more complex economically is limited due to the low productive capacities and sophistication of the economies. For African countries, moving up the complexity ladder is critical for achieving sustainable development goals and reducing vulnerability to external shocks. This requires a critical examination of several macroeconomic factors, among which migration and factor mobility are substantial, especially where international factor movements remain almost uncontrollable. This empirical study therefore explores how migration and factor mobility influence economic complexity, diversification, and sophistication across low-, lower-middle-, and upper-middle-income African countries based on 2024 World Bank income classifications. The study employs panel-corrected standard errors (PCSE), feasible generalised least squares (FGLS), and the Dumitrescu-Hurlin non-causality test to achieve its objectives using a balanced panel of 34 African countries. The findings show that net migration generally hinders economic complexity, while remittances inflows enhance economic complexity in Africa especially in lower-middle-income countries. Also, foreign direct investment (FDI) inflows have no significant influence on economic complexity due to its concentration in the primary and extractive sectors, whereas FDI outflows promote it by fostering domestic firms' capabilities. Also, high net foreign assets hinder economic complexity due to capital being held abroad rather than invested domestically. The study contributes to knowledge by underscoring the need for policies that retain and effectively utilise domestic capital, mitigate brain drains, strategically attract FDI, and leverage remittances for productive investments. By addressing these factors, African countries can enhance their economic complexity, leading to more robust and diversified economies.